2009
DOI: 10.1590/s0103-84782009005000088
|View full text |Cite
|
Sign up to set email alerts
|

Metais pesados em amostras biológicas de bovinos

Abstract: Heavy metals in cattle biological samples RESUMO O objetivo deste trabalho foi determinar a concentração de metais pesados no sangue (Pb, Ni e Cd), soro (Cu e Zn), pelo e leite (Pb, Ni, Cd, Cu e Zn) ABSTRACTThe aim of this research was to determine the heavy metals concentration in blood (Pb, Ni and Cd), serum (Cu and Zn), hair and milk (Pb, Ni, Cd, Cu and Zn)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…In our study, we found that serum copper concentration in animals from both the organic and conventional farm was low (0.072 and 0.146 μg/mL, respectively), which indicates that all the animals analysed were deficient in this element. Much higher concentrations of Cu were reported for dairy cows in Brazil (0.74 μg/mL on average) by de Souza et al [30] and for cows in Turkey (0.78 μg/mL on average) by Erdogan et al [31] and Yokus and Cakir [32]. Souza et al [30] reported that Cu concentration in cows from an unindustrialised area averaged 0.756 μg/mL (range 0.367-1.427 μg/mL), which is ten times that found in our study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our study, we found that serum copper concentration in animals from both the organic and conventional farm was low (0.072 and 0.146 μg/mL, respectively), which indicates that all the animals analysed were deficient in this element. Much higher concentrations of Cu were reported for dairy cows in Brazil (0.74 μg/mL on average) by de Souza et al [30] and for cows in Turkey (0.78 μg/mL on average) by Erdogan et al [31] and Yokus and Cakir [32]. Souza et al [30] reported that Cu concentration in cows from an unindustrialised area averaged 0.756 μg/mL (range 0.367-1.427 μg/mL), which is ten times that found in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Much higher concentrations of Cu were reported for dairy cows in Brazil (0.74 μg/mL on average) by de Souza et al [30] and for cows in Turkey (0.78 μg/mL on average) by Erdogan et al [31] and Yokus and Cakir [32]. Souza et al [30] reported that Cu concentration in cows from an unindustrialised area averaged 0.756 μg/mL (range 0.367-1.427 μg/mL), which is ten times that found in our study. In the case of cows kept in the vicinity of ironworks, Cu concentration ranged from 0.520 to 3.072 μg/mL (0.931 μg/mL on average).…”
Section: Discussionmentioning
confidence: 64%
“…Em um trabalho em que se analisou leite in natura em áreas industrializadas e não industrializadas, detectouse Pb nas amostras de leite na área industrializada e diferenças significativas (P<0,05) não foram verificadas entre épocas de amostragem (verão e inverno) 19 . As concentrações médias e máximas de Pb obtidas na área industrializada foram inferiores ao valor de referência para animais criados em áreas livres de contaminação pelo metal, que é de 0,02 μg.mL -1 .…”
Section: Introductionunclassified
“…No Brasil, tem-se realizado alguns estudos sobre o tema 16,17,19,[28][29][30] . Contudo, as pesquisas no Brasil envolvendo a contaminação no leite animal ou humano por elementos traço tóxicos representam apenas 0,95 % na base ISI considerando as palavras-chave "milk and metals", porcentagem aproximada encontrada também na base Scopus.…”
Section: Introductionunclassified
“…Várias pesquisas (MARÇAL et al, 2003;SOUZA et al, 2009;ROGGEMAN et al, 2013;CANTY et al, 2014) são realizadas focando a transferência de metais contaminantes presente no solo para os animais, tanto por meio de contaminação direta ou via vegetação com consequências impactantes na qualidade da carne bovina. Atualmente, a poluição do ambiente por metais pesados é um sério problema (ATSDR, 2011;OGUNDIRAN et al, 2012), o qual tem sido reconhecido em vários países do mundo.…”
Section: Introductionunclassified